Negative feedback system to maintain cell ROS homeostasis: KEAP1-PGAM5 complex senses mitochondrially generated ROS to induce mitophagy. Issue 9 (2nd September 2022) - Zeb, Akbar; Choubey, Vinay; Gupta, Ruby; Veksler, Vladimir; Kaasik, Allen
ABSTRACT: If cellular reactive oxygen species (ROS) production surpasses the intracellular antioxidant capacity, thus altering the ROS homeostasis, the cell needs to eradicate faulty mitochondria responsible for these excessive ROS. We have shown that even moderate ROS production breaks the KEAP1-PGAM5 complex, inhibiting the proteasomal removal of PGAM5. This leads to an accumulation of PGAM5 interfering with PINK1 processing that sensitizes mitochondria to autophagic removal. We propose that such a negative feedback system maintains cell ROS homeostasis.